Technology-Based Financial Reporting and Internal Control in a Retail Branch: A Case Study of PT Gramedia Jayapura - Catharina Amalia Cantika Larasati; Septyana Prasetianingrum; Adriani Lande; Siti Mariani Basannang; Muhammad Ridhwansyah Pasolo (The Es Accounting And Finance, 2026)
This study examines the use of accounting technology in the preparation of financial statements at PT Gramedia Jayapura. The research is motivated by the need for accurate, timely, transparent, and reliable financial reporting in branch-based retail operations with high transaction volumes, multiple payment channels, and reporting responsibilities to the central office. This study used a descriptive qualitative approach with a case study design. Data were collected through semi-structured interviews, direct observation, and documentation involving three key informants: the assistant manager, finance supervisor, and cashier. Observation focused on sales transaction recording, cashier closing, Z report preparation, cash opname, EDC verification, bank reconciliation, Microsoft 365 data processing, and Power BI monitoring. Data were analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing, with validity strengthened through triangulation and member checking. The findings show that Dynamics 365, Microsoft 365, Power BI, and the point-of-sale system support transaction recording, data classification, bank deposit posting, reporting to the central office, and managerial monitoring. These technologies improve reporting efficiency, data accuracy, transparency, transaction traceability, and decision-making support. However, manual procedures such as cash opname, EDC checking, bank reconciliation, document verification, and managerial approval remain necessary. The main challenges include network instability, system errors, cybersecurity risks, possible data loss, transaction errors, and continuous user adaptation. This study concludes that accounting technology strengthens financial reporting effectiveness when supported by internal control, competent users, stable infrastructure, data security, and continuous managerial supervision.